Proposal of an Energy Based Assessment of Robustness Index of Steel Moment Frames under the Seismic Progressive Collapse - Majid Moradi; Hamidreza Tavakoli (Civil Engineering Infrastructures Journal, 2020)
One of the aims of earthquake engineering is to build secure structures against random loads and also various damage types under lateral loads. Progressive collapse, a word that has attracted attention of many researches after the failure of the World Trade Center, can occur under abnormal loads such as explosion or natural causes like earthquakes. Resistance to progressive collapse is expressed by a parameter called Robustness. The purpose of this study is to survey various methods of calculating robustness index under lateral loads, especially seismic loads, in steel moment frames. So three steel structures with 4, 8 and 15-story and intermediate moment frames were designed and analyzed subsequently. Different methods of measuring the robustness indexes were compared and eventually presented a simple method to assess robustness index based on nonlinear dynamic analysis. Robustness index introduced using this method, which is based on the types of Pancake and Zipper collapses and energy parameters, tries to express an appropriate standard for structural strength against earthquakes.